2021
DOI: 10.3389/fchem.2021.714851
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Switching of Single-Molecule Magnetic Behaviour by Desorption/Adsorption of Solvent Ligand in a New Dy(III)-Based Metal Organic Framework

Abstract: Two metal-organic frameworks (MOFs), [Dy(BDC)(NO3)(DMF)2]n (1, H2BDC = terephthalic acid) and [Dy(BDC)(NO3)]n (1a), were synthesized. The structures of MOFs 1 and 1a are easy to be reversibly transformed into each other by the desorption or adsorption of coordination solvent molecules. Accordingly, their magnetic properties can also be changed reversibly, which realizes our goals of manipulating on/off single-molecule magnet behaviour. MOF 1 behaves as a single-molecule magnet either with or without DC field. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The Dy1 center adopts an octa-coordinated [DyO 8 ] geometry with four O carboxylate atoms (O1, O2, O5, and O6) from three Hm-dobdc 3− ligands, the another O carboxylate atom (O1) and one O phenoxide atom (O3) from one Hm-dobdc 3− ligand, and two O water atom (O7 and O8) from two coordinated H 2 O ( Figure 1B and Supplementary Figure S1 ). Dy−O bond lengths are in the range of 2.287 (3) Å to 2.495 (3) Å, similar to those reported for Dy(III) compounds with oxygen donors ( Supplementary Table S2 ) ( Song et al, 2021 ). Shape analysis revealed that the exact geometry of Dy1 ion can be assigned to a twisted square antiprism ( D 4d symmetry) with a SAPR-8 factor of 1.244 ( Supplementary Table S3 ) ( Ge et al, 2017 ).…”
Section: Results and Disscussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The Dy1 center adopts an octa-coordinated [DyO 8 ] geometry with four O carboxylate atoms (O1, O2, O5, and O6) from three Hm-dobdc 3− ligands, the another O carboxylate atom (O1) and one O phenoxide atom (O3) from one Hm-dobdc 3− ligand, and two O water atom (O7 and O8) from two coordinated H 2 O ( Figure 1B and Supplementary Figure S1 ). Dy−O bond lengths are in the range of 2.287 (3) Å to 2.495 (3) Å, similar to those reported for Dy(III) compounds with oxygen donors ( Supplementary Table S2 ) ( Song et al, 2021 ). Shape analysis revealed that the exact geometry of Dy1 ion can be assigned to a twisted square antiprism ( D 4d symmetry) with a SAPR-8 factor of 1.244 ( Supplementary Table S3 ) ( Ge et al, 2017 ).…”
Section: Results and Disscussionsupporting
confidence: 83%
“…Moreover, the high coordination number and flexible coordination geometry of Dy(III) ions can produce various interesting frameworks. Up to now, multifarious Dy-CPs with slow magnetic relaxation behaviors have been developed ( Wu et al, 2020 ; Song et al, 2021 ; Su et al, 2021 ). Nevertheless, the inherent magnetisms of Dy(III) ions are very sensitive to various factors such as coordination geometry, magnetic interactions, etc., making the performance of Dy(III)-based SMMs difficult to predict ( Pinkowicz et al, 2015 ; Zhang et al, 2015 ; Ge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Dy–O bond lengths are in the range of 2.3015(2)–2.4710(2) Å, comparable to those reported values for Dy III frameworks with oxygen donors (Table S2). The bond length of Dy–O water (2.4206 Å) is slightly longer than the average bond length of Dy–O carboxylate (2.3713 Å). Shape analysis using the SHAPE 2.1 software reveals that the coordination geometry of Dy III center can be described as a slightly distorted low-symmetry Muffin ( C s symmetry) with an agreement MFF-9 factor of 1.043 (Table S4), which is common for 9-coordinated lanthanide species. , Two Dy III centers are connected through four carboxylate groups to form [Dy 2 (CO 2 ) 4 ] binuclear cores, and the separation between two Dy III ions is 4.099 Å (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…This calculated result implies that the relaxation does not reach the first excited state, which may be due to the rapid under-barrier relaxation process caused by anharmonic phonons. 58–60 The main magnetic axis of the ground state for the Dy( iii ) site is directed toward the phenolic hydroxyl groups (O1) from the L 2− ligand, and thus the N atoms (N1 and N3) from the L 2− ligand and the Cl − anion can be considered as the equatorial sites of the coordination environments for Dy1( iii ) (Fig. S16†).…”
Section: Resultsmentioning
confidence: 99%